Learning Strategies at SD Muhammadiyah 1 Waru During Covid-19 Pandemic - Mas Abdul Syakar Dimas Muwaffiq; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
Education has a urgent role in the development of a nation, including the Indonesian nation. Learning strategy is a plan, method and set of activities that are planned to achieve learning objectives. SD Muhammadiyah 1 Waru has good learning and technological facilities that support it. However, during the COVID- 19 pandemic, there has been a change in learning strategies in the teaching and learning process. Muhammadiyah 1 Waru Elementary School during the COVID- 19 pandemic uses online and offline learning strategies. So that teachers are required to be more creative and able to use technology well. This research uses descriptive qualitative research methods. . The technique of collecting data in this research is through interviews, documentation, and observation, while the triangulation used in this study is technical triangulation. From the results of the research that I made in this regard, it can be concluded that SD Muhammadiyah 1 Waru uses online and offline learning strategies. The online system is used for low grades, namely 1, 2, 3 and 4. The offline system is used for high grades, namely grades 5 and 6.